Efficacy and safety of transarterial chemoembolization with CalliSpheres® Microspheres in head and neck cancer - Gao, Fei; Gao, Jinqi; Wang, Kuiyang; Song, Lei (Frontiers in Surgery, 2022)
Objective Transarterial chemoembolization with CalliSpheres® Microspheres (CSM-TACE) presents favorable efficacy and tolerable safety in several cancers, while its application in head and neck cancer (HNC) is unclear. Thus, the current pilot study aims to evaluate the efficacy and safety of CSM-TACE in treating HNC. Methods A total of 15 HNC patients receiving CSM-TACE at the Second Affiliated Hospital of Dalian Medical University from March 2017 to December 2021 were enrolled in this study. Moreover, treatment information, treatment response, progression-free survival (PFS), overall survival (OS), changes in liver and renal function indices, and adverse events were recorded. Results There were nine patients receiving CSM-TACE as first-line treatment and six patients receiving CSM-TACE as second- or above-line treatment; meanwhile, there were seven, seven, and one patient undergoing one time, two times, and three times of CSM-TACE, respectively. Furthermore, the objective response rate (ORR) and the disease control rate (DCR) were 60.0% and 100%, respectively, at the first month; meanwhile, the ORR and the DCR were 53.3% and 73.3%, respectively, at the second month. Moreover, the 1-year PFS rate was 34.1%, and the 1-year OS rate was 38.9%. Additionally, no change in liver function indices (namely, total protein, albumin, total bilirubin, alanine aminotransferase, and aspartate aminotransferase) or in renal function indices (namely, creatinine and blood urea nitrogen) was found before and 1 month after treatment (all P > 0.05). Meanwhile, no severe adverse events were found during and after CSM-TACE. Conclusion CSM-TACE illustrates favorable treatment response and survival benefits as well as a tolerable safety profile in HNC patients.